The relationship between newcomers' emotional labor and service performance: the moderating roles of service training and mentoring functions. Issue 19 (28th October 2018) - Chi, Nai-Wen; Wang, I-An
Abstract: Retaining newcomers and enhancing their service performance are critical issues for the human resource management and hospitality management fields. However, newcomers have just begun to learn the organizational display rules and often encounter more emotional problems than veteran employees. Thus, how organizations help the newcomers to manage their emotions in order to deliver better service is an important issue. Based on the Job Demands-Resources (JD-R) model, this study explores the relationship between newcomers' emotional labor and service performance, and examines whether human resource practices such as service training and mentoring functions can moderate this association. We collected data from hospitality newcomers and their supervisors from 34 hotels. A total of 244 valid paired questionnaires were collected during two different time phases. The results of hierarchical regression analysis show that newcomers' deep acting positively relates to service performance and service training can enhance this relationship. In addition, mentoring functions also differentially moderate the relationships between the two emotional labor strategies and service performance.